Negative 18F-FET PET/CT in brain metastasis recurrence: a teaching case report - Samirah Alshehri (SpringerOpen, 2021)
Abstract Positron emission tomography (PET) using O-(2-[18F]fluoroethyl)-L-tyrosine (18F-FET) PET has been shown to be a useful tool for differentiating radiation therapy outcomes, such as brain metastasis recurrence or radiation necrosis. We present the case of a female patient with brain metastases from pulmonary mucinous adenocarcinoma with suspicion of tumor recurrence on follow-up magnetic resonance imaging (MRI) after radiosurgery. 18F-FET PET/computed tomography (CT) was indicative of radiation necrosis. Due to the patient's medical history and the discrepancy between the brain MRI and PET/CT results, surgical biopsies were decided, which were positive for brain metastasis recurrence. The diagnosis of metastasis recurrence may also be challenging on 18F-FET PET/CT. In case of discrepancies between MRI and PET/CT results, false-negative 18F-FET PET/CT remains a possibility and requires careful follow-up or biopsy.